Metacognitive Strategies: A Foundation for Early Word Spelling and Reading in Kindergartners With SLI. (March 2017) - Schiff, Rachel; Nuri Ben-Shushan, Yohi; Ben-Artzi, Elisheva
This study assessed the effect of metacognitive instruction on the spelling and word reading of Hebrew-speaking children with specific language impairment (SLI). Participants were 67 kindergarteners with SLI in a supported learning context. Children were classified into three spelling instruction groups: (a) metalinguistic instruction (ML), (b) ML that integrates metacognitive strategies (MCML), and (c) a control group. Letter naming, letter sounding, word spelling, and word recognition were assessed at pretest and posttest. Findings from spelling and reading tests as well as interviews indicated that both the ML and MCML groups made statistically significant gains in all measures, whereas the control group did not. However, children with SLI who received training in metacognitive strategies significantly outperformed those who received ML alone in spelling and reading skills. This study provides evidence that children with SLI benefit from applying of metacognitive strategies to spelling practices when acquiring early spelling and reading skills.